Real-World Efficacy and Safety of Tafluprost in Primary Open-Angle Glaucoma Patients with Corneal Disorders: A Taiwan Experience. (29th October 2022) - Lin, Ju-Kuo; Wei, Fu-Tsung; Liu, Yi-Chun; Yen, Yung-Chang
Abstract : Purpose . To investigate the efficacy and safety of switching to 0.0015% tafluprost ophthalmic solution with reduced benzalkonium chloride (BAK) on primary open-angle glaucoma (POAG) patients with corneal disorders under 0.005% latanoprost treatment. Material and Methods . This was a single-arm, open-label, switching study on adult POAG patients treated with latanoprost 0.005% for more than 3 months, with corneal disorders but no dry eye therapy. All patients were switched to tafluprost 0.0015% and followed up for 3 months. The primary outcome was the change in fluorescein staining score (National Eye Institute/Industry [NEI] score) at the end of the study. Secondary outcomes included changes in intraocular pressure (IOP), tear break-up time (TBUT), hyperemia score, and other ocular and nonocular adverse events. Results . Of the 20 patients initially enrolled, 17 patients, all with POAG, completed the study. At the end of the study, the mean NEI score significantly decreased by 1.8 ± 2.2 (p < 0.01 ). No significant changes in IOP were observed (12.8 ± 4.6 mmHg at baseline vs. 12.3 ± 4.0 mmHg on visit 2; p = 0.470 ). TBUT increased by 1.2 ± 1.7 seconds (p < 0.05 ). The proportions of patients with no sign of hyperemia on the bulbar and palpebral conjunctiva increased from 58.5% to 64.7% at baseline (before switching to tafluprost treatment) to 94.1% and 94.1%, respectively, after switching to tafluprost treatment. Dry eye sensation scores were significantly reduced (p < 0.05 ), while other ocular symptom scores did not change significantly. Conclusion . Switching to tafluprost 0.0015% significantly improved fluorescein staining score, TBUT, and conjunctival hyperemia while maintaining IOP control among POAG patients with corneal disorders.